STUDI KOMPARATIF TERHADAP PRINSIP DAKWAH AL-QUR - Yuna Ulfah Maulina, Yuna Ulfah Maulina (IAIN Palangka Raya, 2021)
This paper attempted to examine the Islamic and Christian conflicts caused by da'wah or missions to spread religion by referring to the source of the da'wah call, namely the Qur'an and the Bible, and then compared them with the aim of finding common ground for the origin of the conflict. This research was a qualitative research (library research). The data were processed and analyzed by comparative descriptive method. The results showed that: first, Islam and Christianity were da'wah religions because it was evidenced from two holy book sources that both religions had verses calling to spread their religion. Second, after being investigated, the source of the conflict between Islam and Christianity was caused by certain elements who preached or conveyed religious but ignoring the prevailing ethics. Third, after tracing and reviewing and comparing the two sources of reference for the two religions, both Islam (Al-Qur'an) and Christianity (gospel) never justified da'wah carried out in an impolite way or cause a bloodshed. In contrast,